Huni at pakpak mga dula, mga sanaysay - Cleto, Luna Sicat 1967- (Diliman, Quezon City The University of the Philippines Press, 2022)
Plays and essays on social conditions in the Philippines.
Includes bibliographical references.
In Filipino and some texts in English.
Keywords: Filipino drama; Filipino essays